STRATEGI MEMPERTAHANKAN INDONESIA SEBAGAI PRODUSEN UTAMA PALA DUNIA / The Strategy to Maintain Indonesia as a Main Nutmeg Producer in the World - Bariot Hafif (Badan Penelitian dan Pengembangan Pertanian, 2021)
Indonesia is currently still the world’s prime exporter of nutmeg. Meanwhile, the quality requirements demanded by the world market continue to increase that needs Indonesian intention seriously. This article reveals the performance of Indonesian and global nutmeg production, competitiveness and potential, challenges and opportunities of Indonesia to survive as the major world’s producer and supplier of nutmeg. In 2019, Indonesia produced 37 thousand tons and exported 20 thousand tons to fill 52 thousand tons of the nutmeg world market, with India (12 thousand tons), Sri Lanka (3 thousand tons), and other countries. Unfortunately, Indonesian nutmeg price is lower than Grenada and India, even European Union (EU), the USA, and Japan rejected Indonesian nutmeg 54 times from 2014 to 2016. Indonesia’s potential as a major producer of nutmeg is still good because this commodity is an indigenous plant of Indonesia, the land and climate are suitable for the nutmeg development, and the cultivation method is in line with GAP (Good Agricultural Practices). The challenge is that the quality standard of nutmeg products is getting higher, so be necessary to develop the farmers to meet the standard. The strategy to maintain Indonesia as the world’s main nutmeg producer and supplier is; 1) increasing the intensity of assistance to improve farmers knowledge regarding quality, health, food safety, and sustainable production as well as post-harvest technology, 2) improving professionalism, skill, and adequacy of assistant officers, 3) continuing to encourage nutmeg cultivation following GAP, and 4) lessons learned from the country of Grenada in policy intervention to improve quality, product diversification, and product safety of nutmeg.Keywords: Myristica fragrans, production, export, quality AbstrakIndonesia saat ini masih berstatus sebagai eksportir utama pala dunia. Sementara itu, persyaratan mutu pala di pasar dunia terus meningkat yang perlu mendapat perhatian serius agar Indonesia tetap menjadi produsen utama pala. Artikel ini mengungkapkan tren produksi pala Indonesia dan dunia, daya saing, potensi, tantangan, dan peluang untuk bertahan sebagai produsen dan pemasok utama pala dunia. Pada tahun 2019 Indonesia menghasilkan 37 ribu ton pala dan mengekspor 20 ribu ton untuk mengisi 52 ribu ton pasar pala dunia, bersama India (12 ribu ton), Srilangka (3 ribu ton), dan beberapa negara lainnya. Sayangnya, harga pala Indonesia lebih rendah dari pala Grenada dan India, bahkan pada tahun 2014-2016 terjadi 54 kasus penolakan ekspor pala Indonesia ke Uni Eropa, Amerika Serikat, dan Jepang. Potensi Indonesia sebagai produsen utama pala masih baik karena komoditas ini merupakan tanaman asli Indonesia, lahan dan iklim sesuai untuk pengembangan pala, dan cara budi daya sejalan dengan GAP (Good Agricultural Practices). Tantangan yang dihadapi adalah semakin tingginya standar mutu produk pala di pasar dunia sehingga perlu pembinaan petani untuk memenuhi standar tersebut. Strategi untuk mempertahankan Indonesia sebagai penghasil dan pemasok utama pala dunia adalah sebagai berikut: 1) meningkatkan intensitas pendampingan agar petani lebih paham terhadap aspek mutu, kesehatan, keamanan pangan, keberlanjutan produksi, dan pengelolaan pascapanen untuk memperbaiki mutu pala; 2) memperbaiki profesionalitas, kecakapan, dan kecukupan petugas pendamping; 3) mendorong petani untuk mengikuti budi daya pala sesuai GAP; dan 4) mengambil pembelajaran dari Grenada dalam mengintervensi kebijakan untuk meningkatkan produksi, mutu, diversifikasi, dan keamanan produk pala.Kata kunci: Pala, produksi, ekspor, mutu